Prevalence and Molecular Epidemiology of Intestinal Colonization by Multidrug-Resistant Bacteria among Hematopoietic Stem-Cell Transplantation Recipients: A Bulgarian Single-Center Study - Denis Niyazi; Stoyan Vergiev; Rumyana Markovska; Temenuga Stoeva (MDPI AG, 2024)
Background/Objectives: Intestinal colonization by multidrug-resistant (MDR) bacteria is considered one of the main risk factors for invasive infections in the hematopoietic stem-cell transplant (HSCT) setting, associated with hard-to-eradicate microorganisms. The aim of this study was to assess the rate of intestinal colonization by MDR bacteria and their microbial spectrum in a group of post-HSCT patients to study the genetic determinants of beta-lactam and glycopeptide resistance in the recovered isolates, as well as to determine the epidemiological relation between them. Methods: The intestinal colonization status of 74 patients admitted to the transplantation center of University Hospital "St. Marina"-Varna in the period January 2019 to December 2021 was investigated. Stool samples/rectal swabs were screened for third-generation cephalosporin and/or carbapenem-resistant Gram-negative bacteria, methicillin-resistant Staphylococcus aureus (MRSA), vancomycin-resistant enterococci (VRE), and Stenotrophomonas maltophilia. Identification and antimicrobial susceptibility testing were performed by Phoenix (BD, Sparks, MD, USA) and MALDI Biotyper sirius (Bruker, Bremen, Germany). Molecular genetic methods (PCR, DNA sequencing) were used to study the mechanisms of beta-lactam and glycopeptide resistance in the collected isolates, as well as the epidemiological relationship between them. Results: A total of 28 patients (37.8%) were detected with intestinal colonization by MDR bacteria. Forty-eight non-duplicate MDR bacteria were isolated from their stool samples. Amongst them, the Gram-negative bacteria prevailed (68.8%), dominated by ESBL-producing Escherichia coli (30.3%), and followed by carbapenem-resistant Pseudomonas sp. (24.2%). The Gram-positive bacteria were represented exclusively by Enterococcus faecium (31.2%). The main beta-lactam resistance mechanisms were associated with CTX-M and VIM production. VanA was detected in all vancomycin-resistant enterococci. A clonal relationship was observed among Enterobacter cloacae complex and among E. faecium isolates. Conclusions: To the best of our knowledge, this is the first Bulgarian study that presents detailed information about the prevalence, resistance genetic determinants, and molecular epidemiology of MDR gut-colonizing bacteria in HSCT patients.